Neural and endocrine regulation of osmoregulatory organs in tick: Recent discoveries and implications - Kim, Donghun; Šimo, Ladislav; Vancová, Marie; Urban, Joshua; Park, Yoonseong (General and comparative endocrinology, 2019)
Ticks can survive in harsh and fluctuating vegetated environments for long durations between blood feedings with highly developed osmoregulatory mechanisms. Like the unique life history of hematophagous ticks, osmoregulatory organs and their regulatory mechanisms are significantly different from those in the closely related insect taxa. Over the last ten years, research has uncovered several neuropeptidergic innervations of the primary osmoregulatory organ, the salivary glands: myoinhibitory peptide (MIP), SIFamide, and elevenin. These neuropeptides are thought to be modulators of dopamine's autocrine or paracrine actions controlling the salivary glands, including the activation of fluid transport into the lumen of salivary acini and the pumping and gating action of salivary acini for expelling fluids out into salivary ducts. These actions are through two different dopamine receptors, D1 receptor and invertebrate D1-like dopamine receptor, respectively. Interestingly, MIP and SIFamide are also involved in the control of another important excretory/osmoregulatory organ, the hindgut, where SIFamide is myostimulatory, with MIP having antagonistic effects. FGLamide related allatostatin is also found to have axonal projections located on the surface of the rectum. Investigations of the osmoregulatory mechanisms of these critical vector species will potentially lead to the development of a measure to control tick species.
Keywords: Animals; orgánová specificita; biologické modely; Fluorescent Dyes; slinné žlázy; klíště; axony; Salivary Glands; Endocrine System; Models, Biological; Dopamine; neurony; fluorescenční barviva; Osmoregulation; Neurons; osmoregulace; dopamin; Organ Specificity; zvířata; endokrinní systém; Ixodes; Axons